Xarqueada : ficção e documento no romance de Pedro Wayne - Longhi, Ana Maria (My University, 2014)
This paper looks forward to understand the representations of charqueada (salted and dried meat) industry in Rio Grande do Sul, from the novel Xarqueada, published by Pedro Wayne in 1937. It discusses the novel‘s cultural context, as much as its sociohistorical conditions. In the 1930‘s, the state of Rio Grande do Sul experienced important economic, social and politic al changes that can be read from the changes in literature. Therefore, the concept of representation is privileged, from both the perspectives of the novel‘s documental nature and fictional resources. Concepts like fiction and document, and subjects like regionalist literature and ―romance de 30‖ are considered. This discussion is tributary from the theoretical and methodological approaches from the New Cultural History.
Este trabalho busca compreender as representações do ambiente saladeril no Rio Grande do Sul no romance Xarqueada, de Pedro Wayne, publicado em 1937. É analisado o contexto social em que o romance se insere, bem como as condições sócio-históricas em que foi publicado. O Rio Grande do Sul, nos anos trinta, passava por grandes modificações econômicas, políticas e sociais e, a partir do estudo do romance, é possível perceber a presença destas mudanças na ficção. O conceito de representação é privilegiado, buscando compreender a natureza ficcional e documental do romance. Conceitos como ficção e documento, temas como a literatura regionalista e o romance de 30 são estudados, em uma análise que se torna possível devido ao auxílio das ferramentas teórico-metodológicas disponibilizadas pela Nova História cultural.
Keywords: Wayne, Pedro; Literatura sul-rio-grandense; Literatura brasileira